(3GdedNU (B((3edNU GdbhGfjf aj GdfMh(B)s - (3CHhGdMSjf YHjO Gddg Hf CMeO Hf YHjO Gddg GHf CHj GdQHjY GdbQTj GdCehj GdYKeGfj GdGTHjdj,J (B688 (3g` s ((3CMeO Hf CMeO Hf YHOGddg Hf Ydj GdchS GdTgjQ HbSHg s)
(3ChdgG (B:s
(3Gdcde LeY cdeI hgj GddaXI GdOGdI Ydi eYfi hgj JfbSe KdGKI CbSGe GSe haYd hMQa s
(3BNQgG (B:s
(3hEOZGegG aj Gdfhf Cbd eeG PcQ, hEfeG bd dCf Gdfhf JOZe aj NeSI CMQa ceG JbOe s
(3GdfSNI LRAGfs
(3ajg VHWs
(3HgG fXGe GdJYbjHIs
(3HChdgG hOGNdgG agQS dCHhGH GdcJGH haUhdg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdfMhs